2012
DOI: 10.5194/acp-12-5807-2012
|View full text |Cite
|
Sign up to set email alerts
|

On the representation of immersion and condensation freezing in cloud models using different nucleation schemes

Abstract: Abstract. Ice nucleation in clouds is often observed at temperatures > 235 K, pointing to heterogeneous freezing as a predominant mechanism. Many models deterministically predict the number concentration of ice particles as a function of temperature and/or supersaturation. Several laboratory experiments, at constant temperature and/or supersaturation, report heterogeneous freezing as a stochastic, timedependent process that follows classical nucleation theory; this might appear to contradict deterministic mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 79 publications
2
59
0
Order By: Relevance
“…For most natural samples, the sample heterogeneity indeed leads to a large spread of nucleation efficiencies of sites and the temperature dependence is likely to exceed the time dependence . This was confirmed by a sensitivity study per-formed by Ervens and Feingold (2012) and is in agreement with Welti et al (2012), who found the time dependence to be of minor importance for immersion freezing experiments with kaolinite particles. Therefore, a singular or deterministic approach to describe ambient ice-nucleating particles in models may be appropriate and justified.…”
Section: Introductionsupporting
confidence: 84%
“…For most natural samples, the sample heterogeneity indeed leads to a large spread of nucleation efficiencies of sites and the temperature dependence is likely to exceed the time dependence . This was confirmed by a sensitivity study per-formed by Ervens and Feingold (2012) and is in agreement with Welti et al (2012), who found the time dependence to be of minor importance for immersion freezing experiments with kaolinite particles. Therefore, a singular or deterministic approach to describe ambient ice-nucleating particles in models may be appropriate and justified.…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, a cloud parcel model would be unable to accurately predict the freezing onset or the temperature range over which freezing occurs using a single n s curve obtained from high concentration data. This has important consequences for the accurate simulation of the microphysical evolution of the cloud system under study, such as the initiation of the WegenerBergeron-Findeisen and the consequent glaciation and pre-cipitation rates (Ervens et al, 2011;Ervens and Feingold, 2012). Figure 11 shows the range of n s values for illite NX mineral compiled from 17 measurement methods used by different research groups, the details of which are described by Hiranuma et al (2015a).…”
Section: Dependence Of G On Inp Sizementioning
confidence: 99%
“…Ervens and Feingold (2012) tested different nucleation schemes in an adiabatic parcel model and found that critical cloud features, such as the initiation of the WBF process, liquid water content, and ice water content, all diverged for the different ice nucleation parameterizations. This strongly affected cloud evolution and lifetime.…”
mentioning
confidence: 99%
“…The original version of the model was designed to study cirrus clouds by Heymsfield and Sabin (1989), and then warm clouds (Feingold and Heymsfield, 1992;Feingold et al, 1998). In recent years, this model has been modified and applied to investigate various microphysical problems (e.g., Feingold and Kreidenweis, 2000;Xue and Feingold, 2004;Ervens and Feingold, 2012;Yang et al, 2012Yang et al, , 2016Li et al, 2013). In the current version of the parcel model, air pressure (p), parcel height (h), air temperature (T ), water vapor mixing ratio (q v ) and radii of haze and cloud droplets (r i ) are prognostic variables, which are calculated using the variable-coefficient ordinary differential equation solver (VODE) (Brown et al, 1989).…”
Section: Methodsmentioning
confidence: 99%